Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
anti derivative of 4 is 4x
anti derivative of -x is -1/2 x^2
so y = 4x - (1/2)x^2 + C
(can't forget constants when doing anti derivatives xD)
is this what you need?
*edit
Anti-derivative of a Constant [just a number] becomes (constant)*x
for example integral of 5 = 5x + C
Then there is a Power Rule for integrals
integral of (x)^n = 1/(n+1) *(x)^(n+1) + C
for example: integral of x^2 = 1/(2+1) * (x)^(2+1) + C = (1/3)*x^3 + C
anti derivative of -x is -1/2 x^2
so y = 4x - (1/2)x^2 + C
(can't forget constants when doing anti derivatives xD)
is this what you need?
*edit
Anti-derivative of a Constant [just a number] becomes (constant)*x
for example integral of 5 = 5x + C
Then there is a Power Rule for integrals
integral of (x)^n = 1/(n+1) *(x)^(n+1) + C
for example: integral of x^2 = 1/(2+1) * (x)^(2+1) + C = (1/3)*x^3 + C
We have dy/dx = (4-x) dx which is a first order linear ODE
dy = (4-x) dx. Now integrating both sides we get:
y = 4x - 1/2 x^2 + C
which is the answer. Note we only wrote +c once since we can combine arbitrary constants under addition and subtraction with each other.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.